How Drinking Water Supply PPPs Last After 25 Years (1998 – 2023). Does It Work? - PLAMONIA, NICCO; Suryanto, Krishna (Jurnal Teknik Sipil, 2024)
Abstract The PPP/BOT is a product of institutional arrangement. Institutional arrangements related to increasing the coverage of piping water systems are challenged by the socio-technical complexity of the drinking water provision system. The Institutional Development Framework provides opportunities to learn how the institution capable of delivering the precondition of the actor interacts at the preparation level. The operation started from January 1998 to December 2022, departed from 32.69% coverage, and reached only 61% of the target of 95% after 25 years. As a result, the cases confirmed that there could be vast differences between rules in form and rules in use or that the quality of preparation affects the financial and system performances. The more compliance of the collective choice to the constitutional rules that comply with the International Best Practice showed, the better the performances of the PPP/BOT proved. Keywords: Contracting, financial performances, institution, PPP/BOT, system performances Abstract Kerjasama Pemerintah dan Swasta dengan skema Bangun Guna Serah (PPP/BOT) adalah produk institusi. Proses aransemen institusi yang dihadapkan dengan komplesitas sosio-teknis dalam penyediaan air minum perpipaan. The Institutional Development Framework (IAD) membuka peluang untuk mempelajari bagaimana institusi mampu menjadi prakondisi bagi actor yang berinteraksi pada saat penyiapan PPP/BOT. PPP/BOT di Jakarta berjalan mulai pada Januari 1998 dan berakhir pada Desember 2022. PPP/BOT dimulai dengan cakupan 32,69% dan berakhir setelah 25 tahun dengan hanya mencapai 61%, padahal target awal PPP/Bot pada tahun 1998 adalah mencapai target 95% selama 25 tahun kerjasama. Situasi ini menunjukkan ada disparitas signifikan antara kontrak kerjasama yang disepakati dengan implementasi. Focus penelitian menyoroti bagaimana kualitas persiapan memengaruhi kinerja keuangan dan sistem. Kepatuhan actor yang berinteraksi (pilihan kolektif) terhadap peraturan yang baik dan sesuai dengan best practice internasional, berkorelasi sngat erat dengan peningkatan kinerja PPP/BOT. Keywords: Kontrak, kinerja keuangan, institusi, PPP/BOT, kinerja sistem.